Knowledge and Attitude of School Teachers on School Health Programme, Biratnagar - Basnet, Anita; Bhandari, Menuka; Mandal, Punam Kumari (Journal of Biratnagar Nursing Campus, 2025)
Background: The School Health Programme is a strategy to promote primary health care services in a school community. The goal of a school health program is to ensure students’ physical, mental and social well- being throughout their schooling years. Teachers play a critical role in the effectiveness of this program, as their involvement and support. In Nepal, the School Health Programme is considered an important component of achieving the goal of “Education for All”. The objective of this study was to find out the level of knowledge and attitude regarding the school health Programme among teachers of a school in Biratnagar. Methods: A descriptive cross-sectional study was conducted in the selective schools of Biratnagar, Morang. 103 School Teachers were selected as the sample using a non-probability, purposive sampling technique. The structured Self-administered questionnaire was used to collect the data. Data was analyzed using descriptive statistics, e.g. frequency, percentage, mean, median, standard deviation and inferential statistics (chi-square test) was used to assess the association of knowledge with selected demographic variables. Results: The findings of the study have shown that out of 103 respondents, most of them (85.4%) had adequate knowledge of the school health programme, and almost all teachers had a positive attitude regarding the school Health programme. A significant association was found between knowledge level and educational qualification, with a p-value less than 0.05. Conclusion: The study concluded that the majority of school teachers have good knowledge and a positive attitude toward the School Health Program, which favor the school students’ health and outcomes.